2004
DOI: 10.1590/s1679-62252004000200006
|View full text |Cite
|
Sign up to set email alerts
|

Host-parasite interactions between the piranha Pygocentrus nattereri (Characiformes: Characidae) and isopods and branchiurans (Crustacea) in the rio Araguaia basin, Brazil

Abstract: In the tropics, studies on the ecology of host-parasite interactions are incipient and generally related to taxonomic aspects. The main objective of the present work was to analyze ecological aspects and identify the metazoan fauna of ectoparasites that infest the piranha, Pygocentrus nattereri. In May 2002, field samples were collected in the rio Araguaia basin, State of Goiás (Brazil). A total of 252 individuals of P. nattereri were caught with fishhooks and 32.14% were infested with ectoparasite crustaceans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 17 publications
1
23
0
6
Order By: Relevance
“…Many parasitic crustacean species have preferences for particular sites on hosts in comparison with others (FRYER, 1968;DOUELLOU & ERLWANGER, 1994;CARVALHO et al, 2004;THATCHER, 1998THATCHER, , 2006TAVARES-DIAS et al, 2011SMIT et al, 2014), but this degree of restriction varies among parasite species. Thus, we found that while the lernaeid P. gamitanae infested only the oral cavity and gills of its host characids, L. cyprinacea is a parasite with low specificity that prefers the integument and gills of its hosts.…”
Section: Host-parasite Distribution Patternmentioning
confidence: 99%
See 4 more Smart Citations
“…Many parasitic crustacean species have preferences for particular sites on hosts in comparison with others (FRYER, 1968;DOUELLOU & ERLWANGER, 1994;CARVALHO et al, 2004;THATCHER, 1998THATCHER, , 2006TAVARES-DIAS et al, 2011SMIT et al, 2014), but this degree of restriction varies among parasite species. Thus, we found that while the lernaeid P. gamitanae infested only the oral cavity and gills of its host characids, L. cyprinacea is a parasite with low specificity that prefers the integument and gills of its hosts.…”
Section: Host-parasite Distribution Patternmentioning
confidence: 99%
“…These results clearly showed a change of site preference in C. macropomum, for some unknown reason. Both feeding and attachment sites probably play important roles in the distribution of native ectoparasite crustaceans in host fish (FRYER, 1968;DOUELLOU & ERLWANGER, 1994;THATCHER, 1998THATCHER, , 2006CARVALHO et al, 2004;SMIT et al, 2014). Thus, one important reason why parasites prefer specific sites may relate to more effective use of resources such as food, the host species available and the vulnerability of the attachment site.…”
Section: Host-parasite Distribution Patternmentioning
confidence: 99%
See 3 more Smart Citations